Tindak Tutur Ujaran Ustaz Basalamah Mengenai Pengharaman Wayang - Wilda Fizriyani (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2022)
This article aims to reveal the locutionary and illocutionary forms of utterances made by the religious figure Ustaz Khalid Zeed Abdullah Basalamah, commonly known as Ustaz Basalamah, about the prohibition of wayang. To analyse the data, listening and recording techniques were used from the recorded question and answer between Ustaz Basalamah and the congregation regarding the prohibition of wayang. At the data analysis stage, the distributional method was used by emphasizing the lingual unit of the language that was the target of the research. Through various stages of analysis, the researcher found two of the five types of illocutionary speech acts in Searle's (1969) theory of Ustaz Basalamah's utterances. The two types of illocutionary speech acts are assertive and directive. In the assertive illocutionary act, the researcher found at least five utterances that fall into that category. Meanwhile, four utterances are included in the type of directive illocutionary speech act.